2000
DOI: 10.1034/j.1600-0463.2000.d01-13.x
|View full text |Cite
|
Sign up to set email alerts
|

Resident aerobic microbiota of the adult human nasal cavity

Abstract: Recent evidence strongly suggests that the microbiota of the nasal cavity plays a crucial role in determining the reaction patterns of the mucosal and systemic immune system. However, little is known about the normal microbiota of the nasal cavity. The purpose of this study was to determine the microbiota in different parts of the nasal cavity and to develop and evaluate methods for this purpose. Samples were collected from 10 healthy adults by nasal washes and by swabbing of the mucosa through a sterile intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 33 publications
1
63
0
2
Order By: Relevance
“…On the other hand, species of Corynebacterium, Aureobacterium, Rhodococcus and Staphylococcus have been found to be present dominantly. These data suggested that microbiota present in the nasal cavity of adult humans are strikingly different from that of the pharynx [6].…”
Section: Microbes In Nasal Cavitymentioning
confidence: 90%
“…On the other hand, species of Corynebacterium, Aureobacterium, Rhodococcus and Staphylococcus have been found to be present dominantly. These data suggested that microbiota present in the nasal cavity of adult humans are strikingly different from that of the pharynx [6].…”
Section: Microbes In Nasal Cavitymentioning
confidence: 90%
“…Could this perhaps indicate that S. salivarius strains producing both salivaricin A and salivaricin B are particularly well adapted to growth in the nasopharynx? Although S. salivarius is not usually considered to be a predominant member of the nasopharyngeal flora of adults (Rasmussen et al, 2000), in children under the age of 2 it is the second-most-frequently isolated streptococcal species at this site after S. mitis 1 (Könönen et al, 2002). Since S. salivarius is considered to be essentially nonpathogenic, it could be an excellent candidate for possible introduction into the normal nasopharyngeal flora as protection against recurrent AOM.…”
Section: Inhibitory Strain Tongue Microfloramentioning
confidence: 99%
“…Thirty five workers attending the research were in cement factory, thirteen of the workers were found that they have Candida albican as show in table (2).…”
Section: Iii52 Candida Albicanmentioning
confidence: 99%
“…Citrobacter is a genus of Gram-negative coliform bacteria in the Enterobacteriaceae family [25]. In this study one strain of Citrobacter freundii isolated from worker's nose cavity (2.85%) as shown in table (2).…”
Section: Iii53 Citrobacter Freundiimentioning
confidence: 99%
See 1 more Smart Citation